CALCULATION OF ABSORPTION COEFFICIENT OF ORGANIC DYE N719 FOR DYE-SENSITIVE SOLAR CELL (DSSC) - Otamirzayev, Doniyor (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Abstract: The paper presents a review of literature articles devoted to the study of the effect of dye on the operation of solar cells based on titanium oxide. The absorption coefficient of the organic dye based on rhytinium N719 for dye-sensitive solar cells (DSSC) was calculated, and the light path on TiO₂ was calculated based on the Bouguer–Lambert–Beer equation, taking into account the porous structure of the anode layer. It is shown that the effective layer thickness in the porous structure exceeds the physical thickness by 5–10 times, which ensures a high absorption rate of photons in the visible range.